2009
DOI: 10.1560/ijc.49.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Dendronization of Deep‐Cavity Cavitands to Tune Host Solubility

Abstract: Resorcinarene‐based deep‐cavity cavitands (DCCs) are useful components in supramolecular chemistry because their extended cavity enables the encapsulation of relatively large guests. To provide H2O solubility, they have been modified with hydroxyl functionalized dendrons. This has been carried out by the divergent dendronization of aliphatic poly(ester) dendrons through the third dendritic generation. The resultant macromolecule demonstrated the desired H2O solubility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…[45][46][47] The G3 dendrimer was prepared from the precursor compound octol 41 by dendronization with the requisite acetonide-protected anhydride and deprotected with a solid-phase acid resin to give the G1 cavitand. The first example of a neutral watersoluble host in this class of molecule was third-generation (G3) dendrimer 40 (Scheme 13) from the Grayson group.…”
Section: Synthesis Structure and Coatingsmentioning
confidence: 99%
“…[45][46][47] The G3 dendrimer was prepared from the precursor compound octol 41 by dendronization with the requisite acetonide-protected anhydride and deprotected with a solid-phase acid resin to give the G1 cavitand. The first example of a neutral watersoluble host in this class of molecule was third-generation (G3) dendrimer 40 (Scheme 13) from the Grayson group.…”
Section: Synthesis Structure and Coatingsmentioning
confidence: 99%
“…To take a structurally extreme example, Gibb and Grayson have reported on the synthesis of G3 dendritic cavitand 45, the first neutral, water-soluble, self-assembling host. [161][162][163] The coating of this cavitand was efficiently built up in a divergent synthesis using high yielding steps and no chromatography. An analysis of the solubility of the first and second-generation derivatives, those with sixteen and thirty-two hydroxy groups respectively, revealed that sixty-four hydroxy groups were necessary for solubility in pure water.…”
Section: Systems Utilizing the Hydrophobic Effectmentioning
confidence: 99%
“…While the use of benzylidene acetals, and subsequent deprotection using palladium catalyzed hydrogenation was investigated, the reductive conditions led to cleavage of the benzyl esters on the rim of the cavitand. 57 More successfully, the use of an acetonide protecting group on the anhydride monomer, 3, 58 yielded the modified cavitand, 4, and acidic deprotection using a solid-phase acid resin 59 afforded a new cavitand poly-ol, 5, with sixteen hydroxyl groups (Scheme 1). Subsequent repetition of the coupling and deprotection steps enabled the preparation of a series of monodisperse, hydroxyl-rich, dendronized cavitands, 5, 6, and 7.…”
Section: Synthetic Designmentioning
confidence: 99%